Legacy Pemimpin Besar Islam: Inspirasi untuk Kepemimpinan Modern di Indonesia pada Sustainable Development Goals (SDGs) - Hidayat, Syarif (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Across time and culture, this research explores the legacy of great Islamic leaders as pillars of inspiration for building modern leadership in Indonesia, while looking towards the realization of the Sustainable Development Goals (SDGs). With a focus on the values of morality, justice, and service reflected in the leadership of Prophet Muhammad and other prominent Islamic figures, as well as Indonesian leaders from various historical periods, this research aims to formulate practical guidelines for sustainable leadership development. The research methods employed include literature analysis to explore concepts and theories, comparative studies to compare leadership models, and interviews with leadership experts and stakeholders. The result is a deep understanding of how to strengthen inclusive, ethical, and service-oriented leadership structures that effectively respond to the demands of the time and support the holistic achievement of sustainable development goals.